(3CSGSjGJ JShjb GdNOeGJs - (3SajGf(B, (3eSGdJIs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2023)
(3eONd eaGgjej Mhd GdNOeI, NUGFU GdNOeGJ h GdfJGFL GdeJQJHI YdjgG, cPdc JUfja GdNOeGJ hWHjYJgG, eY bQGQGJ GdeRjL GdJShjbj RgQI GdNOeGJ, hCNjQG GdJMdjdGJ GdeQJHWI HGdYQV GdNOej(B.s
(3eQGLY U(B.117s
Keywords: (3GdJShjbs; (3JShjb GdNOeGJs